Vapour-liquid equilibria for argon-methane system. - Maitra, Kalyan Kumar. (University of Ottawa (Canada), 1966)
An apparatus for the determination of vapour-liquid equilibrium data at low temperatures was built and employed. The vapour-liquid equilibrium data for the argon-methane system were obtained at three isothermal conditions, namely, at 122.66, 132.52 and 143.16°K. The experimental equilibrium data were correlated with two constant Redlich-Kister equations. The liquid phase fugacity coefficients for pure methane were calculated from the experimental data. An attempt was made using the theory of interaction and cavitation to predict Henry's law constants.
Keywords: Engineering, Chemical.